Assessment of genetically modified Maize MON 87429 for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2019‐161). (18th November 2022) - ,; Mullins, Ewen; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Naegeli, Hanspeter; Nogué, Fabien; et al.
Abstract: Maize MON 87429 was developed to confer tolerance to dicamba, glufosinate, quizalofop and 2, 4‐D herbicides. The molecular characterisation data and bioinformatic analyses do not identify issues requiring food/feed safety assessment. None of the identified differences in the agronomic/phenotypic and compositional characteristics tested between maize MON 87429 and its conventional counterpart needs further assessment, except for the levels of phytic acid in grains, which do not raise nutritional and safety concerns. The GMO Panel does not identify safety concerns regarding the toxicity and allergenicity of the DMO, PAT, FT_T and CP4 EPSPS proteins as expressed in maize MON 87429. The GMO Panel finds no evidence that the genetic modification impacts the overall safety of maize MON 87429. In the context of this application, the consumption of food and feed from maize MON 87429 does not represent a nutritional concern in humans and animals. The GMO Panel concludes that maize MON 87429 is as safe as the conventional counterpart and non‐GM maize reference varieties tested, and no post‐market monitoring of food/feed is considered necessary. In the case of accidental release of viable maize MON 87429 grains into the environment, this would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of maize MON 87429. The GMO Panel concludes that maize MON 87429, as described in this application, is as safe as its conventional counterpart and the tested non‐GM maize reference varieties with respect to potential effects on human and animal health and the environment.